1996
DOI: 10.1159/000244342
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and Endothelin 1 during Postnatal Life

Abstract: Nitric oxide (NO) is a potent vasodilator produced by endothelial cells. Endothelin 1 (ET-1), another agent made by endothelial cells, is the most potent vasoconstrictor known to date. Endogenous NO and ET-1 may play a part in the normal physiological pulmonary vascular changes during the postnatal period. However, the changes of NO and ET-1 in healthy neonates have not been defined. We determined serum NO metabolites, i.e., nitrites and nitrates, and plasma ET-1 in 19 healthy neonates at birth (cord blood) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…Previous reports had demonstrated high umbilical cord blood levels of ET-1 which were even more pronounced in newborns with birth asphyxia [19,20] leading to a significant negative correlation between ADM levels and pH in cord blood [21]. These observations could indicate that birth stress may be an acute stimulus for the production of ADM and ET-1 in vascular endothelium.…”
Section: Discussionmentioning
confidence: 85%
“…Previous reports had demonstrated high umbilical cord blood levels of ET-1 which were even more pronounced in newborns with birth asphyxia [19,20] leading to a significant negative correlation between ADM levels and pH in cord blood [21]. These observations could indicate that birth stress may be an acute stimulus for the production of ADM and ET-1 in vascular endothelium.…”
Section: Discussionmentioning
confidence: 85%
“…Endo et al (8) found plasma ET-1 concentrations to be threefold higher at birth compared with 5 or 30 days in healthy human neonates, and similar changes have been described in piglets (21). ET-1 blood levels are elevated in patients with pulmonary hypertension and decrease following resolution in persistent pulmonary hypertension of the newborn (24), pulmonary hypertension due to congenital heart disease (18), and pulmonary hypertension due to acute lung injury (19).…”
mentioning
confidence: 73%
“…This study suggests that pulmonary veins are involved in postnatal adaptation and the pathogenesis of pulmonary hypertension. postnatal adaptation; pulmonary hypertension A NUMBER OF ANIMAL AND HUMAN studies suggest a role for endothelin-1 (ET-1) in adaptation to extrauterine life (8,21) and in the pathogenesis of pulmonary hypertension (18). Endo et al (8) found plasma ET-1 concentrations to be threefold higher at birth compared with 5 or 30 days in healthy human neonates, and similar changes have been described in piglets (21).…”
mentioning
confidence: 99%
“…In the pulmonary vasculature, ET A -mediated contraction decreases and ET B1 -mediated NO-dependent relaxation increases with advancing postnatal age [34], suggesting a switch from a constricted to dilated state, which follows the known decrease in pulmonary vascular resistance following birth, allowing for blood oxygenation [35]. In line with this, plasma ET-1 levels peak immediately after birth and then gradually decrease, with concentrations in healthy term newborns more than threefold greater than at 5 or 30 days postnatal age [36][37][38]. In a recent study of preterm newborns [23], a significant increase of ET-1 after birth was observed in very preterm neonates, but not in more mature neonates.…”
Section: Vasoconstrictionmentioning
confidence: 73%